Chemical Composition, Antimicrobial and Antioxidant Activities of Eugenia Dysenterica DC Essential Oil - Danielle C. S. Oliveira; Telma Mary Kaneko; Maria Cláudia Marx Young; Cynthia Murakami; Inês Cordeiro; Paulo Roberto Hrihorowitsch Moreno (Emerging Science Journal, 2018)
Eugenia dysenterica DC is a native species from the Cerrado biome and can be found in several states of Brazil. This study evaluated the chemical composition, antimicrobial and antioxidant activities from the essential oils of a population collected in São Paulo state. Essential oils were obtained by conventional means, and their compositions were analyzed by GC-MS. Screening assays for antimicrobial activity were carried out by the microdilution method and the antioxidant potential was assessed by the DPPH scavenging method. The GC-MS analysis indicated that 52.63% of the essential oil is composed by oxygenated sesquiterpenes and the major compound is (-)-elema-1,3,11(13)-trien-12-ol (24.86%). The antimicrobial assay indicated MIC 42.1 µg/mL for S. aureus and MIC > 10000 µg/mL for the other tested microorganisms, Gram negative bacteria and fungi. The oil showed an IC50 of 5.4±0.632 mg/mL for in the DPPH assay. The essential oil had a different chemical composition from previous studies. The essential oil did not present a potent antioxidant activity. However, it can be considered a promising antimicrobial agent against S. aureus.